Rāmānuja’s cosmopsychist-panentheistic solution to the hard problem of consciousness - Vaidya, Anand Jayprakash (Religious studies, 2026)
Recent decades have seen a renewal of interest in panpsychism as a solution to the hard problem of consciousness. This has, in part, also driven an increase in interest in classical Indian philosophical traditions among analytic philosophers of mind. Many of these cross-cultural studies pertaining to panpsychism (and cosmopsychism) have focused on one particularly influential school of Indian philosophy, Advaita (non-dual) Vedānta, the most famous proponent of which is Śaṅkara. In this work, we would like to consider the view of another influential philosopher and the school that developed based on his view - Rāmānuja (eleventh century CE) and Viśiṣṭādvaita (qualified non-dualism) Vedānta. We argue that a cosmopsychist-panentheistic metaphysics that is motivated by Rāmānuja’s views offers a solution to the hard problem that is preferable to other comparable views and could form the basis for a panentheistic conception of God that is compatible with the reality of the freedom of human selves.